Finishing properties of oil based finishing material with different finishing systems on Sentang (azadirachta excelsa) / Siti Nur Madihah Mohd Fauzi - Mohd Fauzi, Siti Nur Madihah (Faculty of Applied Sciences, 2017)
Finishing Properties of Oil Based Finishing Material with Different Finishing Systems on Sentang (Azadirachta exce/sa) has been studied. The oil based finishes used was Linseed oil and Tung oil applied using rags application methods. Two different finishing systems was used to applied the finishes, for system 1, sealer was used for undercoat applied using brush added oils applied using rags and system 2 was two coat of oils was applied using rags. The objective in this study was to determine the properties of finishing using traditional techniques on wood surface and to identify the performance of coating materials by using different finishing systems. The finishing produced was evaluated by pencil hardness test, contact angle of wettability test, and cross cut tape test according to American Standard Test Method (ASTM). The measurement of samples used in this study is 4 inch x 12 inch x 1 for each testing. The better application of finishing will produce better performance. The finishing systems have helped Tung and Linseed oil to give better performance. To conclude, Tung oil and system 1 showed better properties and performance of finishing.